Distinctive patterns of placental lesions in pre‐eclampsia vs small‐for‐gestational age and their association with fetoplacental Doppler. (14th October 2019) - Paules, C.; Youssef, L.; Rovira, C.; Crovetto, F.; Nadal, A.; Peguero, A.; Figueras, F.; Eixarch, E.; Crispi, F.; Miranda, J.; Gratacós, E.
ABSTRACT: Objectives: To describe placental histopathological findings in a large cohort of pregnancies complicated by pre‐eclampsia (PE) and/or small‐for‐gestational age (SGA), and to investigate their association with fetoplacental Doppler parameters. Methods: This was a prospective observational study of normotensive pregnancies with SGA (defined as birth weight < 10 th centile) ( n  = 184), PE pregnancies with a normally grown fetus ( n  = 102), pregnancies with both PE and SGA ( n  = 120) and uncomplicated pregnancies ( n  = 202). Uterine (UtA), umbilical (UA) and fetal middle cerebral (MCA) artery pulsatility indices (PI) were assessed. The cerebroplacental ratio (CPR) was calculated by dividing MCA‐PI by UA‐PI. Doppler parameters were considered abnormal when UtA‐PI or UA‐PI was > 95 th centile or MCA‐PI or CPR was < 5 th centile. Placental lesions were categorized as vascular (maternal or fetal side), immunoinflammatory or other, according to the 2014 Amsterdam Placental Workshop Group Consensus Statement. Comparison between the study groups was performed using univariate and multiple regression analysis, and logistic regression was used to determine the relationship between abnormal Doppler parameters and placental lesions. Results: Maternal‐side vascular lesions were significantly more common in PE pregnancies with SGA than in the other groups (PE + SGA, 73% vs PE, 46% vs SGA, 38% vs controls, 31%; P  = 0.01) and included mainly two types of lesion: developmental (PE + SGA, 13% vs PE, 5% vs SGA, 3% vs controls, 1.5%; P  < 0.001) and malperfusion (PE + SGA, 70% vs PE, 39% vs SGA, 32% vs controls, 25%; P  = 0.001). In contrast, the incidence of fetal‐side developmental lesions was significantly higher in normotensive SGA pregnancies than in controls and PE pregnancies (PE + SGA, 0% vs PE, 3% vs SGA, 8% vs controls, 2%; P  = 0.001). All cases displayed a lower prevalence of infectious lesions than did controls, with the highest prevalence of immune lesions observed in pregnancies with both PE and SGA (PE + SGA, 18% vs PE, 8% vs SGA, 10% vs controls, 9%; P  = 0.001). All fetoplacental Doppler parameters evaluated were associated with maternal‐side vascular lesions, mainly malperfusion (mean UtA‐PI: odds ratio (OR), 2.45 (95% CI, 1.51–3.97); UA‐PI: OR, 2.05 (95% CI, 1.02–4.47); MCA‐PI: OR, 2.75 (95% CI, 1.40–5.42); CPR: OR, 1.75 (95% CI, 1.04–2.95)). This association was evident mainly in the normotensive SGA group, being non‐significant in controls or PE pregnancies without SGA. No significant associations were observed between fetoplacental Doppler parameters and other placental lesions in any of the study groups. Conclusions: PE and SGA are associated with different patterns of placental histopathological lesions in accordance with the clinical manifestation of the placental disorder (maternal vs fetal). Fetoplacental Doppler findings show an association with placental malperfusion lesions on the maternal side, supporting the use of abnormal Doppler as a surrogate for placental insufficiency. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.